Evolução temporal da linha de costa segundo uma análise geoespacial de dados de satélite nas adjacências da desembocadura do Rio Jaguaribe - Fortim - Ceará - Perote, Darlyane Rocha do Nascimento (2019)
The erosion process in the coastal zone of Ceará State has been getting worse over time. It is noted that daily a new zone is found in which this process is taking place, due to several factors, which can be anthropogenic, such as disordered urban occupation or natural, such as sea level rise. The coastal zone of Ceará State is characterized by being a space of great appreciation due to its richness and natural beauty, playing an important economic, tourist and social role in the development context of the Northeast region of Brazil. Given the importance of this zone and so many geotechnological tools currently available for a safe monitoring of its evolutionary dynamics, the present study aims to determine the variation of the coastline of the municipality of Fortim of Ceará State and its adjacencies between the years from 1984 to 2018, in order to understand the morphodynamic processes operating in the area, as well as to generate subsidies for efficient coastal management. In the study, the Digital Shoreline Analysis System (DSAS) was used, which makes use of several statistical methods to calculate the variation of the shoreline setback and advance rates, among them the statistical methods NSM (Net Shoreline Movement) and the LRR (Linear Regression Rate), which were chosen for the analysis of the shoreline variation of the present study. Through these were identified progradation snippets and retreat of the coastline, where the results showed that the western portion of the mouth of the Jaguaribe river showed a trend of retreat with small pieces of progradation, and the growth of sandy arrow in the same direction of longshore drift current, and the eastern portion of the mouth showed a retreat trend in the stretch near the mouth, especially on the Fortim beach, in sequence one stabilized area stretch and then presented progradation throughout the rest of the area, towards the beach of Canoa Quebrada. Such retreat and the stabilized area are possibly associated with the wind farm installed in the area, as the area has little occupation and the presence of an extensive dune field.